Effects of task reasoning demand, task condition, types of negotiation, and repair practices on affective variables, language-related episodes, and written output - Ismail, Lilliati (2013)
Considering the growing interest in task-based language teaching,research that investigates the effects of task complexity on second language (L2) development is needed. Currently, there is insufficient classroom-based research that investigates the language learning outcomes that may occur as a result of engaging in tasks of differing reasoning demands in a variety of task conditions. This study aims to fill in some of the gap by investigating the main and interaction effects of two levels of Task Reasoning Demand (TRD) and individual versus dyadic Task Conditions (TC) on learner perceptions of affective factors, as well as the accuracy and syntactic complexity of learner written output. Also, this study investigated the effects of TRD and types of negotiation (negotiation of form versus negotiation of meaning) on frequency of LREs. In addition,this study investigated the effects of TRD and repair practices (self initiated repair versus other-initiated repair, and self-repair versus otherrepair) on the repair outcomes (whether errors were correctly resolved,incorrectly resolved or abandoned). The study draws on the Noticing Hypothesis (1990), the Output Hypothesis (1995), and the Interaction Hypothesis (1996) to rationalise the use of focus-on-form in a task-based context, while Robinson’s Cognition Hypothesis (2007) for task-based language Teaching (TBLT) and Skehan’s Trade-off Hypothesis (2009) underpin the use of task complexity variables to influence language production. The participants were 76 Form six students in a public secondary school in Selangor, Malaysia. Using a quasi-experimental research design incorporating a repeated-measures Latin-square design, participants were randomly assigned to one of four groups. Each group was exposed to all four combinations of the two levels of TRD and two levels of TC, but in different orders. Data were gathered using an affective questionnaire administered after each session, audio-recordings of learner-learner interaction, and learner written output. The data collected were analysed using descriptive statistics, repeatedmeasures MANOVA and repeated-measures factorial ANOVAs. Some of the main findings were that both TRD and TC had significant main effects on learner perceptions of affective factors. Also, the number of LREs during negotiation of form was significantly lower during the +TRD task compared to the –TRD task. Results also showed beneficial effects of learner repair practices in eliciting correct resolutions of errors during LREs. Finally, both TRD and TC had significant main effects on grammatical accuracy and syntactic complexity. TRD and TC also had a significant interaction effect on syntactic complexity. The results provided some empirical and theoretical support for Robinson’s Cognition Hypothesis (2007) and Skehan’s Trade-off Hypothesis (2009). It also highlights the beneficial effects of using learner repair practices in a task-based context. The study also implies that educators should consider the effects of TRD on the frequency of LREs involving negotiation of meaning and negotiation of form when using tasks in the L2 classroom. Finally, the study suggests that, when using tasks in the classroom, educators should consider the effects of TRD and TC on learner affective factors, as well as their effects on grammatical accuracy and syntactic complexity in learner output.